Muscle strength and muscle mass as predictors of hospital length of stay in patients with moderate to severe COVID‐19: a prospective observational study. Issue 6 (14th September 2021) - Gil, Saulo; Jacob Filho, Wilson; Shinjo, Samuel Katsuyuki; Ferriolli, Eduardo; Busse, Alexandre Leopold; Avelino‐Silva, Thiago Junqueira; Longobardi, Igor; de Oliveira Júnior, Gersiel Nascimento; Swinton, Paul; Gualano, Bruno; Roschel, Hamilton; ,
Abstract: Background: Strength and muscle mass are predictors of relevant clinical outcomes in critically ill patients, but in hospitalized patients with COVID‐19, it remains to be determined. In this prospective observational study, we investigated whether muscle strength or muscle mass are predictive of hospital length of stay (LOS) in patients with moderate to severe COVID‐19 patients. Methods: We evaluated prospectively 196 patients at hospital admission for muscle mass and strength. Ten patients did not test positive for SARS‐CoV‐2 during hospitalization and were excluded from the analyses. Results: The sample comprised patients of both sexes (50% male) with a mean age (SD) of 59 (±15) years, body mass index of 29.5 (±6.9) kg/m 2 . The prevalence of current smoking patients was 24.7%, and more prevalent coexisting conditions were hypertension (67.7%), obesity (40.9%), and type 2 diabetes (36.0%). Mean (SD) LOS was 8.6 days (7.7); 17.0% of the patients required intensive care; 3.8% used invasive mechanical ventilation; and 6.6% died during the hospitalization period. The crude hazard ratio (HR) for LOS was greatest for handgrip strength comparing the strongest versus other patients (1.47 [95% CI: 1.07–2.03; P = 0.019]). Evidence of an association between increased handgrip strength and shorter hospital stay was also identified when handgrip strength was standardized according to the sex‐specific mean and standard deviation (1.23 [95% CI: 1.06–1.43; P = 0.007]). Mean LOS was shorter for the strongest patients (7.5 ± 6.1 days) versus others (9.2 ± 8.4 days). Evidence of associations were also present for vastus lateralis cross‐sectional area. The crude HR identified shorter hospital stay for patients with greater sex‐specific standardized values (1.20 [95% CI: 1.03–1.39; P = 0.016]). Evidence was also obtained associating longer hospital stays for patients with the lowest values for vastus lateralis cross‐sectional area (0.63 [95% CI: 0.46–0.88; P = 0.006). Mean LOS for the patients with the lowest muscle cross‐sectional area was longer (10.8 ± 8.8 days) versus others (7.7 ± 7.2 days). The magnitude of associations for handgrip strength and vastus lateralis cross‐sectional area remained consistent and statistically significant after adjusting for other covariates. Conclusions: Muscle strength and mass assessed upon hospital admission are predictors of LOS in patients with moderate to severe COVID‐19, which stresses the value of muscle health in prognosis of this disease.